LACTIC ACID BACTERIA FROM TOFU WASTEWATER AGAINST Staphylococcus aureus - Ni Made Anggun Ciptasari; Ni Nyoman Astika Dewi; I Gusti Agung Dewi Sarihati (Meditory : The Journal of Medical Laboratory, 2026)
Background: Staphylococcus aureus is a pathogenic bacterium that causes skin infections and has been reported to develop resistance to antibiotics. Lactic acid bacteria, which can be isolated from tofu wastewater, have the potential to serve as natural antimicrobial agents through the production of bacteriocins, organic acids, hydrogen peroxide, and carbon dioxide. Objective: To evaluate the antibacterial activity of lactic acid bacteria isolates from tofu wastewater against Staphylococcus aureus. Methods: This descriptive analytic study used purposive sampling. Tofu wastewater samples were collected from 20 tofu factories in Klungkung District. Lactic acid bacteria were isolated on de Man, Rogosa, and Sharpe media, identified through catalase test, Gram staining, and fermentation type test, and tested for antibacterial activity against Staphylococcus aureus using the well diffusion method. Results: A total of 22 isolates of lactic acid bacteria were obtained, characterized as catalase-negative, Gram-positive, with bacilli and cocci morphology, and homofermentative properties. All isolates exhibited antibacterial activity against Staphylococcus aureus with an average inhibition zone diameter of 8.97 mm, categorized as moderate to strong. Conclusions: Lactic acid bacteria isolated from tofu wastewater demonstrated antibacterial activity against Staphylococcus aureus and have potential as natural antimicrobial agents.